Care, Coercion and Dignity at the End of Life. (February 2019) - Russell, Cathriona
End-of-life debates in medical ethics often centre around several interrelated issues: improving care, avoiding coercion, and recognising the dignity and rights of the terminally ill. Care ethics advocates relational autonomy and non-abandonment. These commitments, however, face system pressures—economic, social and legal—that can be coercive. This article takes up two related aspects in this domain of ethics. Firstly, that competence and communication are core clinical ethics principles that can sidestep the overplayed dichotomies in end-of-life care. And secondly, it questions the assumption that advance directives are universally benevolent—comparing the provisions of the Council of Europe's 1999 recommendations on protection of human rights and dignity of the dying within the framework of the Irish context. The article also registers the unintended impacts of changing legal frameworks in relation to euthanasia and assisted suicide in Europe, including recent proposals in the Netherlands. A focus on human dignity can provide a theologically and philosophically shared normative orientation that argues for present directives rather than only advance directives, and a presumption in favour of 'living up to death'. Dignity approaches not only grant rights but secure them by supporting ongoing initiatives that honour, rather than erode, the 'longevity dividend'.